Oral Vaccination With Recombinant Pichia pastoris Expressing Iridovirus Major Capsid Protein Elicits Protective Immunity in Largemouth Bass (Micropterus salmoides) - Yao, Jia-Yun; Zhang, Cheng-Sai; Yuan, Xue-Mei; Huang, Lei; Hu, Da-Yan; Yu, Zhe; Yin, Wen-Lin; Lin, Ling-Yun; Pan, Xiao-Yi; Yang, Gui-lian; Wang, Chun-Feng; Shen, Jin-Yu; et al. (Frontiers in Immunology, 2022)
Largemouth bass iridovirus (LMBV) can cause high mortality and lead to heavy economic loss in the cultivation of largemouth bass, but there was no effective treatment. Here, the present study constructed a recombinant Pichia pastoris expressing LMBV major capsid protein (MCPD). The recombinant GS115-pW317-MCPD was then used to immunize largemouth bass via oral administration, and mucosal immune response mediated by immunoglobulins (Igs) was measured after oral immunization. Serum antibody levels were measured by ELISA, neutralizing antibody titers were determined by serum neutralization test (SNT), antigen presentation-related gene expressions were detected by RT-PCR, and the histopathological characteristics of immunized fish were assessed after challenging with 0.1 ml 107.19 TCID50/ml LMBV. The relative percentage survival (RPS) was also determined. Our results showed that the serum antibody titers of immunized fish were significantly higher than that of control groups (P < 0.05). IgT and IgM expressions in gut were increased significantly after vaccination with GS115-pW317-MCPD; however, much stronger response in gut was observed as compared with gill. The expression levels of major histocompatibility complex (MHC) II, CD8, and T-cell receptor (TCR) were significantly elevated in GS115-pW317-MCPD group (P < 0.05), while CD4 and MHC I transcription levels remained unchanged after oral immunization (P > 0.05). The RPS of fish orally immunized with 1.0 × 108 CFU/g GS115-pW317-MCPD was reached up to 41.6% after challenge with 0.1 ml 109.46 TCID50/ml LMBV. Moreover, orally immunizing with GS115-pW317-MCPD can relieve the pathological damage caused by LMBV. Therefore, GS115-pW317-MCPD showed a promising potential against LMBV.